Pengaruh Social Media Marketing dan Brand Innovativeness terhadap Brand Loyalty dengan Customer Brand Engagement sebagai Variabel Mediasi (Studi Pada Konsumen Citra Body Lotion di Indonesia) - Syahmina Dewi Ghassani; Sri Rahayu Tri Astuti (Faculty of Economics and Business Diponegoro University, 2026)
Amid the rapid growth of social media and intensifying competition in the body care industry, brand loyalty has become a major challenge for established brands in the market. Citra Body Lotion, one of Indonesia's legendary brands, has shown signs of declining brand performance in recent years, accompanied by low engagement rates on its social media platforms that reflect weakening consumer interaction with the brand. Therefore, understanding the factors that drive brand loyalty becomes crucial, particularly through the role of social media marketing and brand innovativeness with customer brand engagement as a mediating mechanism.This study employs a quantitative approach by distributing questionnaires to respondents who meet the criteria as Citra Body Lotion consumers in Indonesia. The sampling technique used is purposive sampling with a total sample of 136 respondents. The collected data were analyzed using Structural Equation Modeling (SEM) with the assistance of AMOS software to examine both direct and indirect relationships among the research variables.The results indicate that social media marketing and brand innovativeness have a positive and significant effect on customer brand engagement. Furthermore, customer brand engagement is proven to have a positive and significant effect on brand loyalty and is able to significantly mediate the relationship between both independent variables. In addition, social media marketing and brand innovativeness also directly and positively affect brand loyalty in a significant manner. This study emphasizes the importance of interactive digital marketing strategies and continuous brand innovation for companies to maintain consumer loyalty in an increasingly competitive digital era.